(untitled) (El Hilo de la Fabula, 2022)
Ada María Elflein Schwarz (1880-1919) was an Argentine writer, daughter of German parents. This granted her the possibility of having a view of Argentina that comes partly from her parents, and partly from her own experience. Being a teacher, journalist, storyteller, she was related to the leading elite of Argentina at the time, while she had a respectable place within the country’s German community. Her travel stories, written in Spanish, show a feminine view of the journey. She was an intrepid traveler, she dared to move like a man and get to places that were hard to reach, which, through her word, became possible for the women of the time. Her hybrid origin is enhanced by her writing of travel stories -a border writing by nature- and, even more, by her feminine gaze, which is clearly present in what is described and narrated.